William Henry Seward correspondence - Seward, William Henry, 1801-1872.
Chiefly letters written by Seward to Samuel B. Ruggles relating to politics and other matters before, during, and after the Civil War.
In part, handwritten transcripts and facsimile.
U.S. senator from and governor of New York and U.S. secretary of state.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ruggles, Samuel B. -- 1800-1881 -- Correspondence; United States. -- Department of State; New York (State) -- Politics and government -- 19th century; United States -- Politics and government -- 19th century; United States -- Politics and government -- 1861-1865.; Cabinet officers; Governors -- New York (State); Public officials -- New York (State); Senators, U.S. Congress -- New York (State)